A new species of Typhonoya Prozorov (Lepidoptera, Lasiocampidae, Lasiocampinae, Gastropachini) from the moist broadleaf forest of the Democratic Republic of the Congo - Prozorov, Alexey M.; Prozorova, Tatiana A.; Mapilanga, Jean Joseph; Hausmann, Axel; Müller, Günter C.; Yakovlev, Roman V.; Volkova, Julia S.; Zolotuhin, Vadim V. (Zootaxa, 2021)
The second species of the genus Typhonoya Prozorov 2011—T. kravchenkoi Prozorov, Müller & Zolotuhin sp. n. from the Democratic Republic of the Congo is described. A previously monotypic genus becomes bitypic. One paratype specimen was collected in the buffer zone of the southern part of the Salonga National Park during a one year-long stationary expedition (June 2017–June 2018). Spread imagoes, heads, legs, venations and genitalia of both species are figured and compared. Additional notes on the genus description and previously known species are added.